G398(P) Fast and meticulous: improving quality of neonatal resuscitation documentation. (12th March 2018) - Karam, M; Merchant, N; Narayanan, S
Abstract : Introduction: Neonatal resuscitation is a fast-paced event that requires cohesive team working and effective multidisciplinary communication. Accurate event documentation is vital for clinical care and has medico-legal implications. Aim: To improve neonatal resuscitation documentation. Methods: One year review of neonatal encephalopathy cases identified a common theme of poor resuscitation documentation (Phase 0). Using quality improvement(QI) methodology (table 1) interventions were implemented in iterative PDSA cycles. Following this, a review of 12 randomly selected resuscitation notes were conducted from July-Dec 2016 (Phase I) and following responsive interventions to findings, a repeat audt was carried out between Aug-Oct 17 (Phase II). Results were analysed in Microsoft Excel. Results: Use of proforma had increased to 73% by phase II. There was 100% documentation of interventions and observations in both phase I and II (table 2). Perinatal staff expressed satisfaction and acceptance of the record form, noting ease of use Conclusion: Through collaborative working and intelligent use of QI methodology >50% improvement in quality of neonatal resuscitation documentation was demonstrate. Further work is needed to improve documentation of team roles and parental communication.